2-Deoxyglycoside Conjugates of Lupane Triterpenoids with High Cytotoxic Activity-Synthesis, Activity, and Pharmacokinetic Profile - Perlikova, Pavla; Kvasnica, Miroslav; Urban, Milan; Hajduch, Marian; Sarek, Jan (Bioconjugate chemistry, 2019)
A set of 41 glycosidic conjugates of pentacyclic triterpenes was synthesized in order to improve the solubility of highly cytotoxic parent compounds. Their in vitro cytotoxic activity was evaluated in 25 cancer cell lines and 2 noncancer fibroblasts. Fifteen compounds had high cytotoxicity on the T-lymphoblastic leukemia cell line CCRF-CEM and 6 of them were active in multiple cell lines of various histogenic origin and not toxic in fibroblasts. Compound 11a had IC50 of 0.64 μM in CCRF-CEM cells, 0.60 μM in K-562 cells, and 0.37 μM in PC-3 cells; compound 12a had IC50 of 0.64 μM in CCRF-CEM cells and 0.71 μM in SW620 cells; compound 17b had IC50 of 0.86 μM in HCT116 cells and 0.92 μM in PC-3 cells. Compounds 11b and 12b were slightly less active than the previously mentioned derivatives; however, their solubility was significantly better, and therefore they were selected for the in vivo evaluation of the pharmacokinetic profile in mice. In both compounds, the maximum concentration in plasma was achieved very rapidly-the highest level in plasma was found 1 h after administration (22.2, respectively, 6.4 μM). For compound 12b, the resorption was followed with fast elimination, and 12 h after administration, the compound was not detected in plasma. In contrast, compound 11b was eliminated more slowly; it was still present in plasma after 12 h, but its concentration dropped below the detection limit after 24 h. The elimination half-time determined for compound 11b was 2.4 h and for compound 12b just about 1.4 h. These values are reasonable for further drug development.
Keywords: glykosidy; Animals; deoxycukry; proliferace buněk; Female; Deoxy Sugars; Tissue Distribution; ženské pohlaví; screeningové testy protinádorových léčiv; Neoplasms; nádory; lidé; Antineoplastic Agents; Mice; protinádorové látky; nádorové buňky kultivované; myši; triterpeny; Tumor Cells, Cultured; Glycosides; tkáňová distribuce; Cell Proliferation; Drug Screening Assays, Antitumor; Triterpenes; zvířata; Humans